Design and implementation of CoLoR architecture control plane based on P4 - Ruohan LIU; Hongbin LUO; Xingbeng WEN (Dianxin kexue)
P4 (programming protocol-independent packet processor) can redefine the fields recognized by the forwarding device and its processing logic through software programming.Aiming at the problems that the new architecture CoLoR faces in actual deployment and improvement,the CoLoR architecture was implemented based on P4,and focused on the implementation of its control plane.The way to use the P4 language to define the header recognition and processing logic of CoLoR architecture-related devices,and to use ONOS (open network operating system) to implement the control mechanism was introduced,and it was deployed in practice to perform functional verification and performance testing.